Efficient Aerial–Aquatic Locomotion With a Single Propulsion System - Tan,YH; Siddall,R; Kovac,M (IEEE Robotics and Automation Letters, 2017)
Aerial-aquatic locomotion would allow a broad array of tasks in robot-enabled environmental monitoring or disaster management. One of the most significant challenges of aerial-aquatic locomotion in mobile robots is finding a propulsion system that is capable of working effectively in both fluids and transitioning between them. The large differences in the density and viscosity of air compared to water means that a single direct propulsion system without adaptability will be inefficient in at least one medium. This paper examines multimodal propeller propulsion using computational tools validated against experimental data. Based on this analysis, we present a novel gearbox enabling an aerial propulsion system to operate efficiently underwater. This is achieved with minimal complexity using a single fixed pitch propeller system, which can change gear underwater by reversing the drive motor, but with the gearing arranged to leave the propeller direction unchanged. This system is then integrated into a small robot, and flights in air and locomotion underwater are demonstrated.